Extended Dust Emission from Nearby Evolved Stars. Issue 1 (1st June 2018) - Dharmawardena, Thavisha E; Kemper, Francisca; Scicluna, Peter; Wouterloot, Jan G A; Trejo, Alfonso; Srinivasan, Sundar; Cami, Jan; Zijlstra, Albert; Marshall, Jonathan P
ABSTRACT: We present James Clerk Maxwell Telescope Sub-millimetre Common-User Bolometer Array 2 (SCUBA-2) $450$ and $850\, μ {\rm m}$ observations of 14 asymptotic giant branch stars (9 O-rich, 4 C-rich, and 1 S-type) and one red supergiant in the solar neighbourhood. We combine these observations with Herschel /PACS observations at $70$ and $160\, μ {\rm m}$ and obtain azimuthally averaged surface-brightness profiles and their point spread function-subtracted residuals. The extent of the SCUBA-2 850 $\, μ {\rm m}$ emission ranges from 0.01 to 0.16 pc with an average of ∼40 per cent of the total flux being emitted from the extended component. By fitting a modified blackbody to the four-point spectral energy distribution at each point along the residual profile we derive the temperature ( T ), spectral index of dust emissivity (β), and dust column density (Σ) as a function of radius. For all the sources, the density profile deviates significantly from what is expected for a constant mass-loss rate, showing that all the sources have undergone variations in mass loss during this evolutionary phase. In combination with results from CO line emission, we determined the dust-to-gas mass ratio for all the sources in our sample. We find that, when sources are grouped according to their chemistry, the resulting average dust-to-gas ratios are consistent with the respective canonical values. However, we see a range of values with significant scatter which indicate the importance of including spatial information when deriving these numbers.